Does CSR contribute to the development of rural young people in cultural tourism of sub-Saharan Africa? Evidence from the Niger Delta in Nigeria - Joseph I. Uduji; Elda N. Okolo-Obasi; Simplice Asongu (African Governance and Development Institute (AGDI), 2018)
Handicrafts are key cultural products consumed in the Nigeria's tourism industry. Owing to low entry barriers, as handicrafts require a low level of capital investment, there is potential to develop viable linkages between tourism and local handicrafts sectors that create economic opportunities for local artisans. Thus, we assess the impact of a new corporate social responsibility (CSR) model of multinational oil companies on the development of rural young people (RYP) in cultural tourism in the Niger Delta of Nigeria. Six hundred RYP were sampled across the rural Niger Delta region. Using the logit model, results indicate that RYP have remained widely excluded from the General Memorandum of Understandings (GMoUs) interventions in cultural tourism projects due to the traditional beliefs that cultural affairs are prerogatives of elders, a caveat to the youths. This implies that if the traditions of the communities continue to hinder direct participation of the RYP from the GMoUs cultural tourism project interventions, achieving equality and cultural change would be limited in the region. The findings suggest that since handicrafts are key cultural products consumed in the tourism industry, GMoUs can play a role in helping to create an appropriate intervention structure that will be targeted towards youth empowerment in the area of traditional handicraft. This can be achieved if the Cluster Development Boards (CDBs) would focus on integrating rural young artisans into local tourism value chains and ensuring that they benefit economically from the sector. The CDBs should aim at creating space for the views of rural young indigenous people's handicrafts; emphasizing the value of indigenous knowledge, particularly on arts and crafts for tourists and expatriate in multinational corporations in Nigeria.
Keywords: 330; Inequality; cultural tourism; handicrafts; corporate social responsibility; multinational oil companies; rural young people; sub-Saharan Africa